PRINSIP TANGGUNGJAWAB PRODUK (PRODUCT LIABILITY) ATAS PENARIKAN KENDARAAN BERMASALAH OLEH PELAKU USAHA DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Novanema Duha; Tan Kamello; Dedi Harianto; Utary Maharani Barus (Universitas Sumatera Utara, 2016)
ABSTRACT Getting proper life and legal protection is right for every citizens, especially consumers. The same is true to product recall; legal protection for consumers is highly needed since there is the liability of a business person of his product. The problems of the research were as follows; how about product liability in the law on consumers and legal protection for consumers could be effective on product recall by a business person, the provision of product recall performed by foreign automotive companies which product marketing was done in domestic market, and the liability of a business person regarding product recall done by him. Keywords: Product Liability, Product Recall.